2011
DOI: 10.1242/jeb.055467
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gene expression profiles for highly similar aggressive phenotypes in male and female cichlid fishes (Julidochromis)

Abstract: SUMMARYJulidochromis marlieri and Julidochromis transcriptus are two closely related Tanganyikan cichlids that have evolved different behavior and mating strategies since they diverged from their common ancestor. While J. transcriptus follows the ancestral pattern of male dominance, male-biased sexual size dimorphism and territoriality, the pattern is reversed in J. marlieri. In J. marlieri, females show all of these behavioral and morphological characteristics. This raises the question of whether female J. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 78 publications
(71 reference statements)
2
27
1
Order By: Relevance
“…If populations possess similar traits, perhaps not surprisingly, the genetic architecture of those traits may also be similar because natural selection may have acted on the same genes that underlie the traits (Campbell and Bernatchez, 2004;Turner et al, 2010;Schumer et al, 2011). We found that the Atlantic salmon had similar genetic architectures (amounts of additive and non-additive effects) for seven out of the nine traits despite having a relatively large F ST value.…”
Section: Energy Conversionmentioning
confidence: 62%
“…If populations possess similar traits, perhaps not surprisingly, the genetic architecture of those traits may also be similar because natural selection may have acted on the same genes that underlie the traits (Campbell and Bernatchez, 2004;Turner et al, 2010;Schumer et al, 2011). We found that the Atlantic salmon had similar genetic architectures (amounts of additive and non-additive effects) for seven out of the nine traits despite having a relatively large F ST value.…”
Section: Energy Conversionmentioning
confidence: 62%
“…; Schumer et al. ) showed differential expression, although not generally in the expected directions. The α‐subunit of the gonadotropins follicle‐stimulating hormone (FSH) and luteinizing hormone (LH) is crucially important to reproductive physiology, including gametogenesis and synthesis of sex steroid hormones in the gonads (e.g., see Maruska et al.…”
Section: Discussionmentioning
confidence: 90%
“…; Schumer et al. ). However, in the present study, the only significant difference in whole brain AVT expression was increased expression in sneakers relative to females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations